Surgical treatment of cervical cancer - Esteves F., Luis (2015)
We presented a table of the different modalities of radical surgical treatment of cancer of the cervix, in its differents clinical stages of evolution. In this paper we present 83 cases that we have treated by radical surgery over 1005 patients with cancer of the cervix attended at the Gynecology Department of I.N.E.N., Lima , Peru, in 2 years and 6 months (June 1952- December 1954). Papel about this was communicated at the Third Interamerican Session of the American College of Surgeons (11th-14th of January 1955, Lima. Peru). We support the doctrine of the radical hysterectomy with bilateral dissection of the pelvic lymph nodes over the knowledge of the forms and ways of propagation of carcinoma of the cervix; of the failure of radiotherapy over the metastatiies nodes, and radioresistance of the lesion. Special emphasis is given over the extension of operation, the surgeon experience and the importance of the hospital organization where this operation is made. Some considerations about operative accident like hemorrhage and the best way to control and prevent it are done. In the same plane we discuss the urinary  complications. Some cases of total and partial exenteration of the pelvic organs are communicated. We emphasize over the pre and post-operative conditions of the patients. In five tables we show the main aspects of our cases.